A comprehensive examination of factors impacting collegiate athletes' utilization of psychological assessment and intervention services. Issue 3 (24th November 2020) - Donohue, Brad; Gavrilova, Elena; Danlag, Alexandra; Perry, Joanne; Kuhn, Corey; Allen, Daniel N.; Benning, Stephen D.
Abstract: Although collegiate athletes underutilize mental health programming, investigators have rarely examined factors that may influence their participation in such programs. The current study examined how structured interviews and demographic factors influence collegiate athletes to use psychological programming. Two‐hundred and eighty‐nine collegiate athletes were referred to the study. They were screened for mental health and randomly assigned to one of two semi‐structured interviews based on experimental phase. Participants in Phase I received standard engagement (SE; N = 35) or SE + discussion of mental health (DMH; N = 44). Phase II participants received SE + DMH ( N = 82) or SE + DMH + discussion of personal ambitions (DPA; N = 66). Phase III participants received SE + DMH + discussion about their culture of choice (DCC; N = 25) or SE + DMH + discussion of sport culture (DSC; N = 37). After receiving the respective interview participants were offered psychological assessment and intervention. χ 2 analyses revealed class standing, mental health symptom severity, referral type, and type of engagement interview influenced program commitment/utilization. Logistic regression analyses indicated SE + DMH + DPA and SE + DMH + DSC uniquely improved assessment attendance whereas referrals from coaches/teammates, participation in sport performance workshops, and senior status uniquely improved assessment and intervention attendance.